Through the prism untold rock stories from the Hipgnosis Archive - Powell, Aubrey 1946- (Thames & Hudson, Inc., 2021)
Founded in 1968 by Aubrey "Po" Powell, Storm Thorgerson and Peter Christopherson, graphic design firm Hipgnosis gained a legendary status by transforming the look of album art through their designs for AC/DC, Black Sabbath, The Police, Genesis, Led Zeppelin, Pink Floyd, Paul McCartney, Syd Barrett, and The Who. In this lively volume, Powell presents brutally honest, entertaining and revealing insider stories from the world of rock, featuring an eclectic cast of pop stars, comedians, actors, managers, gangsters, and inspirational world figures from 1966 on. His thrilling narrative is packed with anecdotes--from the founding of Hipgnosis to surviving drugs busts, and from the creative process behind the most iconic album artworks of all time to mounting the Pink Floyd exhibition, Their Mortal Remains--and is richly illustrated with Hipgnosis artwork and Powell's own photographs. Drama and creativity are the common threads throughout these amazing stories. With candor and insightful reflection, Powell reveals how he and Storm became an effective creative partnership despite their volatile relationship; how the final color artwork for Led Zeppelin's Houses Of The Holy was created; how the most iconic album cover of all time--The Dark Side Of The Moon--came about; and how the 2017 Pink Floyd retrospective became the largest and most successful music exhibition ever mounted by the Victoria and Albert Museum--despite the deeply antagonistic and dysfunctional relationship between Roger Waters and David Gilmour. Throughout, Powell exposes how the trappings of fame and glory upset the balance of everyday life, bringing creativity and destruction in equal measure
"First published in the United Kingdom in 2021 by Thames & Hudson Ltd...First published in the United States of America in 2021 by Thames & Hudson Inc."--Copyright page
Keywords: Hipgnosis -- Körperschaft; Geschichte; Powell, Aubrey; Hipgnosis (Design studio) / Anecdotes; Sound recordings / Album covers / Anecdotes; Rock musicians / Anecdotes; Rock groups / Anecdotes; Rock music / Anecdotes; Disques / Pochettes / Anecdotes; Musiciens rock / Anecdotes; Groupes rock / Anecdotes; Rock (Musique) / Anecdotes; Hipgnosis (Design studio); Rock groups; Rock music; Rock musicians; Anecdotes; Autobiography; Autobiographies; Autobiografie